Targeted treatment for neuroblastoma using methoxyestradiol (2-ME)-loaded mitochondria-targeting immunoliposomes modified by datuximab (anti-GD2) and (L-cyclohexyl alanine-D-arginine)3 ((Fx,r)3) peptide - Mingyu Wan; Zhili Chen; Yueyi Deng; Robert J. Lee; Chengyun Yan (Cancer Nanotechnology)
Abstract The 2-ME therapy encounters significant challenges in practical use. Its low water solubility compromises bioavailability, limiting drug efficacy. In addition, poor stability in the physiological environment hinders sustained therapeutic effects, and insufficient targeting may harm normal tissues, reducing treatment outcomes and patient quality of life. This study aimed to develop mitochondria-targeted immunoliposomes (2-ME/aGD2-F-ILN) loaded with 2-ME and modified by anti-GD2 and (Fx,r)3 peptide. The goal was to improve 2-ME's water solubility and stability while enhancing its targeting ability, thereby resolving critical issues associated with 2-ME therapy and offering a more effective treatment for neuroblastoma. The measurement of physicochemical properties showed that 2-ME/aGD2-F-ILN exhibited a smooth and spherical morphological characteristic, accompanied by excellent dispersibility. The particle sizes, PDI and zeta potentials of 2-ME/aGD2-F-ILN were measured to be 141.0 ± 4.8 nm, 0.186 ± 0.01 and 24.5 ± 2.8 mV, respectively. 2-ME/aGD2-F-ILN could release the drug continuously and slowly, and maintain good stability at 4℃. Cytotoxicity test exhibited that the IC50 of 2-ME/aGD2-F-ILN was 0.34 ± 0.03 µg/mL, compared with free 2-ME, the toxicity of 2-ME/aGD2-F-ILN to SH-SY5Y cells increased by 5.2 times. Western blot analysis showed that 2-ME/aGD2-F-ILN had the more remarkable effect on regulating the expression of Bcl-2, Bax, caspase-3 and caspase-9. JC-1 staining assay showed that 2-ME/aGD2-F-ILN displayed the more obvious green fluorescence, indicating that aGD2-F-ILN’s targeting effect on mitochondria increased the accumulation concentration of 2-ME in cells. Cellular binding and uptake assays suggested that Rho-aGD2-F-ILN could specifically target GD2 positive tumor cells and then further reach their mitochondria. In vivo imaging indicated that the fluorescence intensity of DiR/aGD2-F-ILN at 24 h in tumor was 2.8 times that of free DiR, suggesting that DiR/aGD2-F-ILN exhibited a stronger SH-SY5Y tumor targeting ability in vivo. Therapeutic efficacy indicated that 2-ME/aGD2-F-ILN could better suppress the growth of SH-SY5Y tumor cells in the body with lower toxicity and side effects. The results demonstrates that the 2-ME/aGD2-F-ILN immunoliposomes could improve the antitumor effects of 2-ME and reduce toxic and side effects. The reason might be attributed to the dual modification of liposomes with anti-GD2 and (Fx, r)3 peptide, which were able to target neuroblastoma cells and mitochondria step by step.